Degradable hypercrosslinked porous polymer generated from aromatic polyketone - Handou Zheng; Guangshui Tu; Cheng Du; Heng Gao; Lixia Pei; Haiyang Gao (NPG Asia Materials)
Abstract Although hypercrosslinked porous polymers as highly efficient adsorbents can remove pollutants, hypercrosslinked polymers (HCPs) themselves are also a source of white plastic pollution. Development of degradable HCPs is highly desirable based on the full environmental protection concept. In this paper, we reported the direct synthesis of hypercrosslinked polyketones (HCPK-X, X = H, OtBu) generated from degradable aromatic polyketones via external crosslinking technique. The hypercrosslinked structure of HCPK-X was fully characterized, and HCPK-OtBu had a mesopores structure (1.27–68.5 nm) and large surface area (S BET = 321 m2/g). HCPK-OtBu exhibits a good adsorption capability for aniline removal from aqueous solution, and its enhanced adsorption capability is ascribed to the interactions between aniline and the carbonyl and tert-butoxy groups. The photodegradation of hypercrosslinked polyketones was evaluated and emphasized. The prepared hypercrosslinked polyketones can rapidly and efficiently decompose under UV light irradiation, which represents the first sample of degradable hypercrosslinked polymers.